Structure and function of the eukaryotic ADP-dependent glucokinase : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Biochemistry, Massey University, Manawatu, New Zealand. - Richter, Jan Paul (Massey University, 2014)
The ADP-dependent glucokinase enzymes (ADPGK) are the first new glycolytic enzymes to be discovered in over 40 years. This class of enzymes was first described in thermophilic archaea in 1994. A decade later, an ADPGK from a eukaryote was also identified and characterised. The ADPGK enzymes catalyse a phosphorylation reaction converting glucose and ADP to glucose-6-phosphate and AMP. The enzyme is well studied in extremophilic archaea, where ADPGK is part of a set of glycolytic enzymes that use ADP instead of ATP for the phosphorylation of various sugars. However, ADPGK has also been found in the genomes of mesophilic species and higher eukaryotes, suggesting that the enzyme is not necessarily an adaption to high temperatures. In eukaryotes, ADPGK has been linked to a modified glycolysis pathway that is required for T-cell activation. While crystal structures of the archaeal ADPGKs are known, no structure of a eukaryotic ADPGK had been solved before the work undertaken in this thesis. In this thesis, the kinetic analysis of a recombinant form of Homo sapiens ADPGK and the crystal structure of a truncated form of Mus musculus ADPGK are presented. Both enzymes were expressed recombinantly in E. coli and purified in soluble form. The kinetic parameters determined for H. sapiens ADPGK proved to be comparable to the mouse enzyme, which had been published earlier. In addition, the phosphoryl acceptor specificity of H. sapiens ADPGK was extensively tested by 31P-NMR, where the enzyme proved to be highly specific for Dglucose. Residues important for catalysis have been modified by site-directed mutagenesis and the variants of H. sapiens ADPGK were purified and kinetic parameters determined. A single crystal was obtained from a truncated variant of M. musculus ADPGK, which diffracted to 2.1 Å. The structure of M. musculus ADPGK could be solved by molecular replacement using the known crystal structures of the archaeal ADPGKs for initial phasing. It proved to be quite similar to the archaeal, ADPGKs, despite the low sequence identity. The combined data in this work improves our understanding of the conservation of the structure-function relationship of eukaryotic ADPGKs.
Keywords: Glucokinase; Eukaryotic; ADP-dependent; Research Subject Categories::NATURAL SCIENCES::Biology::Cell and molecular biology::Molecular biology